The effect of corporate environmental initiatives on firm value: evidence from Fortune 500 firms - Wassmer, Ulrich (2014)
When do firms derive value from investing in environmental initiatives (CEIs)? We examine stock market responses to the announcements of 183 CEIs by 71 Fortune 500 firms during the period 2002 to 2008. We find that the stock market reacts positively to such announcements but does not react differently to CEIs concerning a firm’s inputs, throughputs, and outputs. We also find that there is an inverted U-shaped relationship between the timing of a CEI and the abnormal stock market return following its announcement. Overall, this study shows that timing is a relevant explanatory factor for the value firms derive from investing in environmental action.